Gender Bias in Household Educational Expenditure An Econometric Analysis of Bargaining and Budget Share - Lakshmanasamy, T. (JOURNAL OF INDIAN EDUCATION, 2021)
The gender bias in education and household education expenditure is analysed, and the effect of parental bargaining power on the budget share of education in the household expenditure is examined using the 68th round (2011-2012) of NSSO data on Bihar and Kerala. The collective household model and Three Stage Least Square estimation approaches are used. The 3SLS estimates show a significant gender gap in education in rural and urban Bihar and Kerala, but not much difference in the gender allocation patterns of households in the two states. Though urban households allocate more resources for education, gender disparity is more in urban households relative to rural households. The household budget share on education increases with an increase in the proportion of boys than girls. The male bargaining power has some effect on the budget share of household education expenditure in urban households, but not in rural households of Bihar and Kerala.